PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PT. ARTHA ASIA FINANCE DI SEMARANG - Dwi Daryanto, 08.05.51.0001; Suharmanto, Toto (Students Journal of Economic and Management, 2013)
The purpose of business is to create customers in order to feel satisfied. Consumer satisfaction is influenced by the perception of the quality of the service, product quality, price and factors that is personal and that is the situation for a moment. One of the factors that determine customer satisfaction is customer perception about the quality of service that focuses on the five dimensions of quality, services, namely physical evidence, reliability, responsiveness, assurance and empathy. The population in this study was consumers Artha Asia Finance, JL. of Brigjend. Sugiarto No. 462 C, Semarang. And samples in this study was 100. Analysis technique used is regression results showed that: physical evidence, reliability, responsiveness, assurance and empathy matter positively and significantly to consumer satisfaction.Key words : Tangible, reliability, responsiveness, assurance, empathy and consumer satisfaction